Cancer Mortality and Incidence in Cement Industry Workers in Korea - Dong-Hee Koh; Tae-Woo Kim; Seung Hee Jang; Hyang-Woo Ryu (Elsevier, 2011)
Objectives: Cement contains hexavalent chromium, which is a human carcinogen. However, its effect on cancer seems inconclusive in epidemiologic studies. The aim of this retrospective cohort study was to elucidate the association between dust exposure in the cement industry and cancer occurrence. Methods: The cohorts consisted of male workers in 6 Portland cement factories in Korea. Study subjects were classified into five groups by job: quarry, production, maintenance, laboratory, and office work. Cancer mortality and incidence in workers were observed from 1992 to 2007 and 1997-2005, respectively. Standardized mortality ratios and standardized incidence ratios were calculated according to the five job classifications. Results: There was an increased standardized incidence ratio for stomach cancer of 1.56 (27/17.36, 95% confidence interval: 1.02-2.26) in production workers. The standardized mortality ratio for lung cancer increased in production workers. However, was not statistically significant. Conclusion: Our result suggests a potential association between cement exposure and stomach cancer. Hexavalent chromium contained in cement might be a causative carcinogen.